A new mechanistic approach to analysing LEFM fatigue crack growth behaviour of metals and alloys - Lal D.N. (My University, 2025)
Basic features of a new mechanistic approach developed for allowing an improved physical understanding and prediction of the variable-influenced cyclic growth behaviour of LEFM (long) cracks in metals and alloys are presented. The approach is essentially an extension of the one adopted recently for an accurate description of the intrinsic LEFM fatigue-threshold condition. The analysis conditions assumed here are low-strength (or coarse grain) material, room temperature, laboratory air environment, and stress ratio, R = 0, so that the fracture mechanics parameter ΔK or Kmax is the only dominant variable. Three distinct micromechanical modes of fatigue fracture, namely a Kmax-rmcontrolled "submicroscopic cleavage", a ΔK-rmcontrolled "reversed shear" and a Kmax-controlled "microscopic cleavage" or "static" mode operating in a critically stressed zone Vc ahead of the crack tip are postulated to predominate respectively in Stages I, II and III of the log da/dN vs log ΔK fatigue crack growth curve. The two observed transition points between stages are postulated to correspond to a transition in growth mechanisms. The mechanistic differences necessitate description of each stage separately. Assuming Paris-type power-law relations, growth equations for Stages I and II are deduced wherein constants A and m can be estimated theoretically. Model-predicted crack growth curves showed good agreement with experimental data for several steels and aluminium alloys. The approach may be found useful in design situations where a quick, fairly accurate and conservative estimate of fatigue crack growth life is desired. © 1994.